ISOTOPIC COMPOSITION INFLUENCE OF IRRIGATION WATER ON SOME AROMATIC PLANTS - PUŞCAŞ, Romulus; MAGDAS, Dana Alina; LUNG, Ildiko; CRISTEA, Gabriela; SORAN, Maria Loredana; FEHER, Ioana; DEHELEAN, Adriana (Studia Universitatis Babeș-Bolyai Chemia, 2016)
In this paper, three species of aromatic herbs (Petroselinum crispum, Ocimum basilicum, and Origanum vulgare) were investigated, by mean of stable isotopes (deuterium, oxygen and carbon) and total phenol content, in order to study the influence of irrigation water. The results revealed the fact that there is a strong correlation between the isotopic compositions of irrigation water (deuterium enriched water or tap water) and dD, δ18O, d13C values and total polyphenol content of studied plants. Multielemental content was subjected to analysis of variance (ANOVA). It was found that Ocimum basilicum plant was characterized by a higher level of As and Co as compared to other two species, while Origanum vulgare had the highest content of Cu. Also, a correlation between the irrigation water content and toxic metal uptake had shown that the Pb concentration is influenced by the water isotopic composition.